Shifts in composition and function of bacterial communities reveal the effect of small barriers on nitrous oxide and methane accumulation in fragmented rivers - Xing, Chong-Yang; Li, Hang; Li, Qi; Lu, Lun-Hui; Li, Zhe (Frontiers in Microbiology, 2023)
Rivers are often blocked by barriers, leading to fragmentation and the formation of different habitats. However, the effects of low riverine barriers on the accumulation of N2O and CH4 in fragmented-river remain unclear. Here, barriers (less than 2m, MB) increased N2O concentration by 1.13 times and CH4 decreased by 11.8%, while barriers (higher than 2 m, less than 5m high, HB) increased N2O concentration by 1.19 times and CH4 by 2.76 times. Co-occurrence network analysis indicated MB and HB can promote the enrichment of Cyanobium and Chloroflexi, further limiting complete denitrification and increasing N2O accumulation. The MB promotes methanotrophs (Methylocystis, Methylophilus, Methylotenera) to compete with denitrifiers (Pseudomonas) in water, and reduce CH4 accumulation. While the HB can promote the methanotrophs to compete with nitrifiers (Nitrosospira) in sediment, thus reducing the consumption of CH4. Combined with the results of structural equation model simulation and metagenomic analysis, both MB and HB reduce river velocity, increase water depth, and reduce dissolved oxygen (DO), leading to the enrichment of nirS-type denitrifiers and the increase of N2O concentration in water. Moreover, the HB reduces DO concentration and pmoA gene abundance in water, which can increase the accumulation of CH4. In light of the changes in the microbial community and variation in N2O and CH4 accumulation, the impact of fragmented rivers on global greenhouse gas emissions merits further study.